Do trabalho prescrito ao trabalho realizado: uma reflexão sobre aulas de leitura - Ferreira, Ilda (2008)
The present study aims to understand the mechanism professor of public school disposes to work as for the use prescriptions of reading pratices. The components placed under scrutiny are the PCN prescriptions, the lectures given by the professor, the protagonist of this study, and also an interview with hersef. The analysis centers around the identification and interpretation of the compliance and non-compliance levels observed in the work activity regarding the prescriptions. In the field of reading studies, this paper is based on the Kato (1985, 2005), Kleiman (1992, 2000), Rojo (2004) and Possenti (2004). From Language studies, this paper is based on the concept o interdiscourse (Maingueneau, 1984, 1987, 2001) and theoretical formulations on modality notion (Maingueneau, 1991, Koch, 2002). From the Work studies I resorted to notions from activity ergonomy (Amigues, 2002, 2004), ergology (Schwartz, 2000). The results showed the strength of institutional prescriptions as a means to generate of the auto-prescriptions as elements that drive for the use of oneself